Curriculum for ERCP and endoscopic ultrasound training in Europe European Society of Gastrointestinal Endoscopy (ESGE)Position Statement - Gavin Johnson; Webster George; Boškoski Ivo; Campos Sara; Gölder Stefan Karl; Schlag Christoph; Anderloni Andrea; Arnelo Urban; Badaoui Abdenor; Bekkal Noor; Christodoulou Dimitrios; Czakó László; et al. (2021)
The European Society of Gastrointestinal Endoscopy (ESGE) has recognized the need to formalize and enhance training in endoscopic retrograde cholangiopancreatography (ERCP) and endoscopic ultrasound (EUS). This manuscript represents the outcome of a formal Delphi process resulting in an official Position Statement of the ESGE and provides a framework to develop and maintain skills in ERCP and EUS. This curriculum is set out in terms of the prerequisites prior to training; recommended steps of training to a defined syllabus; the quality of training; and how competence should be defined and evidenced before independent practice. 1: Trainees should be competent in gastroscopy prior to commencing training. Formal training courses and the use of simulation in training are recommended. 2: Trainees should keep a contemporaneous logbook of their procedures, including key performance indicators and the degree of independence. Structured formative assessment is encouraged to enhance feedback. There should be a summative assessment process prior to commencing independent practice to ensure there is robust evidence of competence. This evidence should include a review of a trainee's procedure volume and current performance measures. A period of mentoring is strongly recommended in the early stages of independent practice. 3: Specifically for ERCP, all trainees should be competent up to Schutz level 2 complexity (management of distal biliary strictures and stones > 10 mm), with advanced ERCP requiring a further period of training. Prior to independent practice, ESGE recommends that a trainee can evidence a procedure volume of > 300 cases, a native papilla cannulation rate of ≥ 80 % (90 % after a period of mentored independent practice), complete stones clearance of ≥ 85 %, and successful stenting of distal biliary strictures of ≥ 90 % (90 % and 95 % respectively after a mentored period of independent practice). 4: The progression of EUS training and competence attainment should start from diagnostic EUS and then proceed to basic therapeutic EUS, and finally to advanced therapeutic EUS. Before independent practice, ESGE recommends that a trainee can evidence a procedure volume of > 250 cases (75 fine-needle aspirations/biopsies [FNA/FNBs]), satisfactory visualization of key anatomical landmarks in ≥ 90 % of cases, and an FNA/FNB accuracy rate of ≥ 85 %. ESGE recognizes the often inadequate quality of the evidence and the need for further studies pertaining to training in advanced endoscopy, particularly in relation to therapeutic EUS.
Keywords: Általános orvostudomány; Klinikai orvostan